Early evangelicalism: a reader - Yeager, Jonathan (Oxford University Press, 2013)
Early evangelicalism flourished during the transatlantic revivals of the eighteenth century, coinciding with the emergence of the Enlightenment in America and Europe. This anthology introduces a host of important religious figures, providing biographical sketches of each author and over sixty excerpts from a wide range of well-known and lesser-known Protestant Christians.